Biochemistry review : viva case studies and MCQs - U Satyanarayana (Kolkata Books and Allied, 2015)
Chemical constituents of life; physiological biochemistry; metabolisms; clinical biochemistry and nutrition; current topics; nutritional disorders; metabolic diseases/inborn errors; cases related to organ function; cases related to endocrine function; miscellaneous; chemical constituents of life; physiological biochemistry; metabolisms; clinical biochemistry and nutrition; current topics; practical biochemistry-principles; biochemistry iiiusreated.
Keywords: Biochemistry